2006
DOI: 10.1002/jbm.b.30634
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and drug release property of star poly(ϵ‐caprolactone)s with dendritic cores

Abstract: A series of star poly(epsilon-caprolactone)s (PCL) with dendritic cores, PAMAM-PCLs, were synthesized through the ring-opening polymerization of epsilon-caprolactone (CL) initiated by poly(amidoamine) dendrimer (PAMAM-OH). By controlling the feed ratio of the macroinitiator PAMAM-OH to the monomer CL, the star polymers with different branch lengths and properties can be obtained. The successful incorporation of PCL sequences onto the PAMAM-OH core was verified by FTIR, 1H NMR, and combined size-exclusion chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Several studies have reported the enzymatic degradation of PCL by lipase. [11][12][13][14]30 It is apparent from Figure 1 that the degradation of SPCL occurs in the presence of lipase, this enzyme being responsible for only 7.7 AE 1.6% weight loss after 30 days of immersion under dynamic conditions. These results are in accordance with several published studies.…”
Section: Degradation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the enzymatic degradation of PCL by lipase. [11][12][13][14]30 It is apparent from Figure 1 that the degradation of SPCL occurs in the presence of lipase, this enzyme being responsible for only 7.7 AE 1.6% weight loss after 30 days of immersion under dynamic conditions. These results are in accordance with several published studies.…”
Section: Degradation Studiesmentioning
confidence: 99%
“…Several studies have reported that lipase degrades PCL. [11][12][13][14] Lipases are watersoluble enzymes that hydrolyze ester bonds of watersoluble substrates such as triglycerides, phospholipids, and cholesteryl esters. 15,16 The lipase gene family consists of multiple lipases that share a similar sequence structure at the genetic and protein level, thus indicating a common ancestral origin.…”
Section: Introductionmentioning
confidence: 99%
“…During the degradation of the polymeric films short water-soluble fragments are formed. The degradation of PCL is accelerated in bulk studies as well as in 2D monolayer investigations by different types of lipases, for instance the lipase from Porcine pancreas [25], Pseudomonas alcaligenes [26], or Pseudomonas cepacia [27]. Lipases are able to hydrolyze triacylglycerols and other ester bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] We have rigorously studied the self-assembling of synthetic [8,9] and biodegradable [10][11][12][13] nanoparticles and hollow capsules [14,15] for biomedical applications such as drug delivery systems (DDS) and diagnosis. In the use of degradable nanoparticles, there is a limitation due to a lack of response to environmental changes such as pH, temperature, electric, magnetic, and light stimuli.…”
Section: Introductionmentioning
confidence: 99%